Meningkatkan Aktivitas dan Prestasi Belajar Siswa Kelas VIII pada Konsep Sistem Gerak pada Manusia Melalui Model Student Teams Achievement Divisions - Setiawan, Dony; Ayu, Ika (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
This research aims to increase the activity and learning achievement of class VIII students at SMP Negeri 5 Demak for the 2022/2023 academic year. The subjects of this research were class VIII students at SMP Negeri 5 Demak. The type of research carried out was Classroom Action Research (PTK) using two cycles. Data collection techniques include observing the implementation of student learning activities and tests. The instruments used in this research were student learning activity observation sheets and student achievement test sheets. The research results showed that the data on student learning activity results in cycle I reached 72.14% which could be categorized as good, and in cycle II it reached 86.43% in the very good category. Meanwhile, student learning achievement in cycle I, classical completeness achieved by students was 50% and student learning achievement in cycle II with classical completeness achieved by students was 60%. Thus, it can be concluded that the application of the Student Teams Achievement Divisions learning model can increase student activity and learning achievement in class VIII of SMP Negeri 5 Demak in the 2022/2023 academic year.